The Influence of Gross Profit Margin, Operating Profit Margin and Net Profit Margin on the Stock Price of Consumer Good Industry in the Indonesia Stock Exchange on 2012-2014 - Mahruzal Mahdi; Muammar Khaddafi (International Journal of Business, Economics, and Social Development, 2020)
This study aims to analyze the effect on stock prices. Company profit information which includes gross profit margin, operating profit margin, and net profit margin are variables that are thought to affect the 2012-2014 stock prices. The unit of analysis used is the Consumer Good Industry Company. Testing of this research was carried out using the classic assumption test, which consisted of 3 basic assumptions, namely normality, multicollinearity, and heteroscedasticity. After that, a multiple linear regression test is performed to determine the regression equation that shows the relationship of the dependent variable that is determined by two or more independent variables. The F-test is carried out to find out whether the three independent variables together have a significant effect on the dependent variable. And the last t-test is used to see the significance of the influence of individual independent variables on the dependent variable by assuming other variables are constant. The results showed simultaneously a positive and significant influence from net profit margin, operating profit margin, and gross profit margin on stock prices in Good Consumer Industry Company listed on the Indonesia Stock Exchange, while partially net profit margin and gross profit margin were not there is a positive and insignificant influence on stock prices on Good Consumer Industry Company listed on the Indonesia Stock Exchange, while operating profit margin, partially there is a positive and significant effect on stock prices on Good Consumer Industry Company listed on the Indonesia Stock Exchange on 2012-2014.